Faktor-Faktor Yang Mempengaruhi Kesiapan Kerja Mahasiswa Jurusan Akuntansi Politeknik Negeri Padang - Putri Mutia Lestari; Anda Dwi Haryadi; Deddy Djefris (Politeknik Negeri Padang, 2023)
This research was conducted to explain the factors that influence work readiness. This research was conducted on students of the Padang State Polytechnic Accounting Department who are actively studying from class 2019-2021. The research method used is quantitative method by collecting data using a questionnaire and measured using a Likert scale. The factors discussed in this study are abilities, role clarity and motivation. The theory used in this study is the theory of Tam and Utaut. The method of determining the sample using a purposive sampling method with a total sample of 209 respondents. The data analysis method used is multiple linear regression analysis. The results of this study indicate that the variables of ability, role clarity and motivation are factors that influence work readiness.